Influence of senior executives characteristics on corporate environmental disclosures: A bibliometric analysis - Hafiz Muhammad Arslan; Chengang Ye; Bilal; Muhammad Siddique; Yusra Yahya (Journal of Risk and Financial Management, 2022)
This study aims to synthesize the literature on the top management team (TMT) characteristics influence on environmental disclosures of public organizations and identify recent trends, key themes, influential journals, and authors. Our study recruited 88 research articles on the relationship of TMT characteristics and environmental disclosures from 54 academic journals published from 2010 to 2021 for bibliometric analysis. Our study has identified three influential streams: (1) Role of Politically connections of TMT, good governance in environmental disclosures; (2) Significance of environmental disclosures and performance; and (3) institutional investors and environmental disclosures. Thematic map classifies the TMT characteristics and environmental disclosures relationship themes into four categories: Niche theme (e.g., financial expertise, CFO characteristics, CEO tenure, and board backgrounds); motor themes (e.g., environmental sustainability and climate change); emerging/declining themes (e.g., Environmental disclosure, managerial ownership, and CEO tenure); and basic/transversal themes (e.g., CEO characteristics, upper echelon theory, corporate governance). This study assists academicians, policymakers, managers, and consultants in the corporate sector to understand the role of different dimensions of TMT characteristics regarding environmental disclosures. Our study concludes with important practical implications and future research directions.
Keywords: 330; TMT characteristics; environmental disclosures; bibliometric analysis; ESG disclosures; climate change; CEO characteristics